2014
DOI: 10.1111/ijfs.12632
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa polyphenols accelerate vitamin B12 degradation in heated chocolate milk

Abstract: The rate of vitamin B 12 loss was 3X greater in heated, chocolate-flavoured milk than in unflavoured milk. Studies of B 12 stability in the presence of cocoa powder components were performed to identify the reactive agents. Cocoa polyphenols with a strong capacity both for reduction and for peroxide generation accelerated B 12 destruction as much as 20-fold vs. polyphenols without both capacities. Polyphenols with both capacities include the cocoa polyphenol (+)-catechin and oligomers thereof, but also the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 40 publications
3
17
0
Order By: Relevance
“…Berry Ottaway (1993) reported that cyanocobalamin in solution is decomposed by both oxidizing and reducing agents. Johns et al (2015) showed that the generation of reactive oxygen species such as hydroxyl radicals can result in the oxidation of vitamin B12 and its decomposition. In the present study, only four temperature/RH combinations were tested, which was not enough to precisely model the impact of temperature and RH, and to understand the influence of a w and oxidative status on the stability of cyanocobalamin in fortified flours.…”
Section: Discussionmentioning
confidence: 99%
“…Berry Ottaway (1993) reported that cyanocobalamin in solution is decomposed by both oxidizing and reducing agents. Johns et al (2015) showed that the generation of reactive oxygen species such as hydroxyl radicals can result in the oxidation of vitamin B12 and its decomposition. In the present study, only four temperature/RH combinations were tested, which was not enough to precisely model the impact of temperature and RH, and to understand the influence of a w and oxidative status on the stability of cyanocobalamin in fortified flours.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, it has long been known that polyphenols are able to prevent vitamin E oxidation and degradation. 31 A diet fortified with quercetin, epicatechin, or catechin substantially increased α-tocopherol plasma and liver levels in rats. All tested flavonoids protected α-tocopherol from oxidation in human low-density lipoprotein (LDL) ex vivo and reduced concentrations of α-tocopheroxyl radicals.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 94%
“…In vitro , it has long been known that polyphenols are able to prevent vitamin E oxidation and degradation . A diet fortified with quercetin, epicatechin, or catechin substantially increased α-tocopherol plasma and liver levels in rats.…”
Section: Micronutrientsmentioning
confidence: 99%
“…35 An appreciable loss of B 12 occurs during the storage, thermal processing, and fermentation of milk. 23,25 Recently, Johns et al 36 found that the rate of B 12 loss was three times greater in chocolate-flavored milk (approximately 33.5%) than in unflavored milk (approximately 15%) during heat treatment (1 h at 100 C). The increased loss of B 12 in chocolate-flavored milk was attributable to cocoa polyphenols that readily form peroxides.…”
Section: Milkmentioning
confidence: 99%
“…The increased loss of B 12 in chocolate-flavored milk was attributable to cocoa polyphenols that readily form peroxides. 36…”
Section: Milkmentioning
confidence: 99%